The Loweramudarya economic region of Uzbekistan peculiarities in the territorial structure of economy (Journal of Geography and Environmental Management, 2019)
The Loweramudarya economic region of Uzbekistan peculiarities and changes in the territorial structure of economyhave been analysed, the area economic axis, factorial and Christallerian regular placing schemes interaction, formingclusters, region poles and growth lines have been defined in the paper. The growth of productive forces concentrationin nodes and along lines has been predicted.